A consistent finite element formulation for laminated composites with nonlinear interlaminar constitutive law. (1st September 2020) - Lolić, Damjan; Zupan, Dejan; Brojan, Miha
Abstract: We introduce a consistent displacement-based finite element formulation for the analysis of laminated composites with nonlinear interlaminar constitutive law. The computational model includes the nonlinear Reissner beam for modelling the bulk material and continuously distributed system of nonlinear springs to describe the connection between layers. We can introduce general functions for describing the stiffness of springs. Therefore, our model is able to describe a variety of physical phenomena, such as friction between layers, contact, cohesive forces, etc. The displacement field on which the stiffness function depends upon is expressed in a local, deformed basis. Distributed force which results from the interaction between layers, is introduced into the governing equations in order to avoid the need for additional interface elements and to simplify the numerical solution method. Precise experiments on thick partially delaminated beam, solid beam, shear lap joint beams and film-substrate composite as well as comparison with the results from the literature, demonstrate the efficiency and versatility of the proposed numerical procedure.